PTH-102 Ferric maltol, unlike ferrous sulphate, does not adversely affect the intestinal microbiome. Issue 2 (June 2019) - Mahalhal, Awad; Mansfield, John; Sampson, Mark; Lewis, Stephen; Lamb, Chris; Frau, Alessandra; Pritchard, DM; Probert, Chris
Abstract : Introduction: We have previously shown that altering dietary ferrous iron consumption exacerbates murine models of inflammatory bowel disease ( Mahalhal et al., 2018 ) and is associated with dysbiosis. We have now investigated the effect of oral ferric maltol and ferrous sulphate on the microbiome of patients with iron deficiency anaemia (IDA) and on mice treated with dextran sodium sulphate (DSS) to induce colitis. We report results of changes at the phylum level. Methods: Studies were performed on three groups of wild-type mice: acute colitis was induced with 2% DSS for 5 days, followed by 5 further days on water while mice were fed one of three diets (from day-1 of DSS treatment): normal diet (200ppm iron ferrous sulphate) [ND (n=8)], 400ppm iron ferrous sulphate [FS (n=16)] or 400ppm iron ferric maltol [FM (n=16)]. Clinical and pathological data were compared at day-1 and day-10, when faecal samples were collected. 16 patients with IDA were also recruited: 10 were treated with FS and 6 with FM supplements for 4 weeks: paired faecal samples (pre and post-treatment) were collected. Faecal bacterial gDNA was extracted from murine and human samples and the microbiota composition was determined from the sequence of V4 region of 16 S rDNA. Statistical inferences were made using Welch's t-test with post-hoc analysis: Shannon Diversity Index (SDI) and Principal Component Analysis (PCA) were used to compare population and phylum-level changes. Results: DSS-induced colitis was worse in ND and FS mice than FM mice (determined by weight loss [3, 7 & 0%, at day-8 respectively] and histology [median score 2, 2 & 1 at day-10]). FS supplementation was associated with an increase in Bacteroidetes (15% in mice, 4% in humans) whereas FM led to a reduction in Bacteroidetes (3% in mice and 15% in humans). There was a 4% increase in Firmicutes with FM supplementation in mice and 20% in humans whereas FS led to a 15% reduction in Firmicutes in mice and 5% in humans. Conclusion: This study has demonstrated differential and unique influences of ferric maltol and ferrous sulphate supplements on the faecal microbiome of mice with DSS induced colitis and patients with iron deficiency. These differences might contribute to the difference in side effects that are associated with these preparations.